African philosophy, culture, and traditional medicine - Makinde, M. Akin (Athens, Ohio : Ohio University center for international Studies, 1988)
For over two centuries, Western scholars have discussed African philosophy and culture, often in disparaging, condescending terms, and always from an alien European perspective. Many Africans now share this perspective, having been trained in the western, empirical tradition. Makinde argues that, particularly in view of the costs and failings of western style culture, Africans must now mold their own modern culture by blending useful western practices with valuable indigenous African elements. Specifically, Makinde demonstrates the potential for the development of African philosophy and even African traditional medicine. -- back cover
Ifa, Knowledge, and Probability -- On Philosophy and Culture -- The Question of African Philosophy -- On Philosophy in General -- A Short History of African Philosophy -- First Phase: Unwritten Philosophy and Unknown Philosophers -- Second Phase: Re-orientation in Philosophy and Colonial Ethnophilosophers -- Third Phase: Critical Re-orientation in Philosophy and the Contemporary African Philosophers -- Who is an African Philosopher? -- The Social and Political Philosophy of Obafemi Awolowo -- The Regime of Mental Magnitude: The Philosophical Foundation of Awolowo's Socialism -- The Universal Mind -- Marxist Totalitarianism and Capitalism's "Totalitarian" Democracy -- African Traditional Medicine: Principles and Practice -- African Traditional Practice Among the Yoruba of Nigeria
Includes bibliographical references (pages 141-149) and index
Keywords: Philosophy, African; Traditional medicine -- Africa, Sub-Saharan; Medicine, Traditional -- Africa South of the Sahara; Africa, Sub-Saharan -- Civilization